On the construction of the system for forensic psycholinguistics - Yang, Shaogang; Liu, Zhuo (Filozofia Publiczna i Edukacja Demokratyczna, 2019)
Forensic psycholinguistics is an emerging interdisciplinary subject that makes use of the psychological methods to analyze the linguistic phenomena in legal activities and therefore it is of the multiple and cross-disciplinary nature. In ancient Chinese culture there were written expressions with thoughts of forensic psycholinguistics and its practices. In Western countries the research started from European societies at the end of 19th century when Münsterberg and Cattell and some other scholars acted as the pioneers of this domain. After the WWII the research center of forensic psycholinguistics gradually moved to the United States where the research of legal psychology and the use of psychological methods greatly facilitate the study and practices of forensic psycholinguistics. Its study object aims at the linguistic behavior in such legal activities as legislation, judicial, the obeying of the law and transgression, and its task should be the research on the behavior of the legal language in both levels of consciousness and unconsciousness. The construction of the system for forensic psycholinguistics should start from the perspectives of linguistic psychology of legislation, judicial, the enforcement and obeying of the law and the legal publicity so that a cross-cultural emerging subject with its values of practical application could be created.